Effectiveness of e-learning implementation as a distance learning strategy during coronavirus disease (covid-19) pandemic - Dedi Prestiadi (Universitas Muhammadiyah Surabaya, 2020)
Abstract. This study aims to determine the effectiveness of the implementation of elearning as a distance learning strategy during pandemic coronavirus disease (Covid-19).The effectiveness will be examined from the results of previous studies through metaanalysis methods Meta-analysis is the study of several research results in a similar study. The unit of analysis in the study of meta-analysis of these are documents written are taken from the journals the results of the research are purposive in accordance with the theme of research on the implementation of e-learning in the process of learning. The primary research instrument is there on the researchers themselves aided by the guidance documentation. Data analysis that was carried out was the analysis of quantitative and qualitative data. Quantitative analysis is used to analyze data in the form of numbers and the percentage of e-learning effectiveness. Qualitative data analysis is used for the study of data in the form of descriptive data about the implementation of e-learning. The results showed that the implementation of e-learning was effective as a distance learning strategy during coronavirus disease (Covid-19) pandemic.Keywords: E-learning, distance learning, Coronavirus Disease (Covid-19)